Pusa Green: a new bathua variety - Yadav, R K; Tomar, B S (Indian Horticulture, 2019)
Chenopodium (Chenopodium album), commonly known as bathua, grow as a weed and consumed as leafy vegetable. It is not only nutritive, but also, one of the cheapest leafy vegetables available in winter season. It is a store house of vitamins such as carotene (precursor of vitamin A), ascorbic acid (precursor of vitamin C), folic acid and riboflavin as well as minerals such as iron, calcium and phosphorous. Bathua can be used as a potential food crop for diversification of agriculture to newer areas, environmental sustainability and for combating the nutritional deficiency in human being in many parts of the world. This underutilized crop does not require high inputs and can be easily grown on marginal lands. Seeing its potential as a cheap source of antioxidants and other nutrients, nutritionally rich and high-yielding genotype Pusa Green with good quality components has been released.